IMPLEMENTATION OF TECHNOLOGY BASED SCIENCE LITERATION IN IMPROVING STUDENT'S CRITICAL THINKING ABILITY ON SCIENCE LEARNING AT SD 04 RANTAUPRAPAT LABUHANBATU DISTRICT - Rismawati Lubis; Rosmawaty Rosmawaty; Sri Listyarini (SENSEI RESEARCH CENTER, 2021)
This type of research is descriptive qualitative. The purpose of this study was to analyze the application of technology-based scientific literacy in improving students' critical thinking skills in science learning at SD 04 Rantauprapat. Objects were obtained by purposive sampling. The object in this study was taken as many as 56 for respondents, namely fourth grade students of SD Negeri 04 Rantauprapat, namely Class IVA totaling 28 students and Class IVB totaling 28 students for a questionnaire of students critical thinking abilities. The ability to think critically of students in this case includes Reason, Situation, Clarity, Overview, and Inference with the acquisition of technology-based scientific literacy in science learning at SD 04 Rantauprapat, namely: student frequency those who think that the Reason aspect is above an average of 48 students or 92.9%; the frequency of students who think the Situation aspect is above the average of 46 students or 82.1%; the frequency of students who think that the clarity aspect is above the average is 46 students or 82.1%; the frequency of students who think about the Aspects of Examination (Overview) is above the average of 34 students or 60.7%; and the frequency of students who think inference (Inference) above the average is 34 students or 60.7%. Based on the analysis of students 'scientific literacy abilities made in written tests and interviews, it can be seen how the students abilities in solving science questions. The results are as follows. a) almost all students' science content is still low, this means that most students do not understand the concept of science, b) recognize scientific questions, there are no errors for all students, c) in identifying scientific evidence and phenomena, all students are able to read the data provided, d) in drawing conclusions, almost all students are able to do well, e) in communicating conclusions, almost all students are able to do it well, f) almost all students show understanding of concepts, g) in science applications, almost all students are able to apply them well